The Influence of Organizational Commitment and Job Stress on Job Satisfaction is Mediated by Employee Workload at BPJS Employment in the Aceh Region - Rahmatika, Andrija; B, Mesra (Lafadz Jaya Publisher, 2023)
This research aims to see the influence of organizational commitment and work stress on workload and job satisfaction positively or negatively. This research was carried out with associative quantitative research. This research was carried out at BPJS Employment in the Aceh region. The population used was 100 employees because all the population wanted to used as a sample, the sampling technique used is a saturated sample and the model used is analysis method. The data collection techniques used are questionnaires and surveys. Based on the results of the research that has been carried out and data analysis as explained in the previous chapter, the following conclusions from the research results are presented as follows: Workload has a negative and insignificant effect on Job Satisfaction, this is proven in the Path Coefficients table with original sample values of -0.120 and Pvalues 0.265 > 0.05. Organizational Commitment has a negative and significant effect on Work Load, this is proven in the Path Coefficients table with an original sample value of -0.169 and a P value of 0.000 < 0.05. Organizational Commitment has no significant positive effect on Job Satisfaction, this is proven in the Path Coefficients table with a sample original value of 0.686 P values 0.000 < 0.05. Job Stress has a positive and significant effect on Work Load, this is proven in the Path Coefficients table with an original sample value of 0.176 P value 0.003 < 0.05. Job Stress has a positive and significant effect on Job Satisfaction, this is proven in the Path Coefficients table with an original sample value of -0.004 P value 0.978 > 0.05. Workload is not able to be an intervening variable and has a positive and insignificant effect on Organizational Commitment and Job Satisfaction. This is proven in the Path Coefficients table with an original sample value of -0.021 P value 0.288 > 0.05. Workload is not capable of being an intervening variable and has a negative and significant effect on Job Stress and Job Satisfaction. This is proven in the Path Coefficients table with an original sample value of 0.188 P values 0.001 < 0.05.